Extent of market diversification in Malaysia furniture export - Low, Shi Qin (2019)
The rapid growth of the Malaysian furniture industry had successfully transformed a cottage-based industry into a multi-billion Ringgit industry. Malaysian furniture exports value had exceeded RM10 billion in year 2017 and ranked as 9th largest furniture exporter in the world in 2017. Thus, this research was conducted to identify the 10 most important markets for Malaysian furniture exports that have contributed more than 70% of total export from 2010 to 2017 and the main reasons to why other markets have not been successful as furniture importer from a manufacturers’ perspective in order to increase the furniture exports. The first objective conducted by using secondary data while second objective conducted by using questionnaire. The results for first objective showed that the top 10 important markets were United States of America (USA), Japan, Singapore, Australia, United Kingdom (UK), India, Canada, Philippines, United Arab Emirates (UAE) and Saudi Arabia and have contributed 72.70% of total export from 2010 to 2017. The result for the second objective concluded that customer buying power as most important reason, followed by competitive with other country’s furniture exporter, shortage of raw material, less innovation in furniture design, government policy implementation and lastly do not consider foreign market preferences.